Dual‐Band Electrochromic Smart Window for Dynamic Switching Between Radiative Cooling and Solar Heating - Xinyu Zhao; Qixiang Chen; Fan Fan; Qiliang Wang; Yuehong Su; Minsu Liu; Fahua Zhu; Dongliang Zhao (Advanced Science)
Abstract Electrochromic smart windows can actively modulate their reversible transition between transparent and opaque states, adapting to varying climatic conditions and thereby offering a sustainable solution for energy‐efficient buildings. However, the operational range of current electrochromic smart windows is mostly limited to the solar spectrum. Expanding this range into the mid‐infrared spectrum could significantly enhance their energy‐saving capabilities. In this study, a dynamic electrochromic (EC) glass that integrates silver electrodeposition/dissolution with mechanical flipping of the glass panel is designed. This design enables bidirectional dynamic modulation of both the solar spectrum (0.3–2.5 µm) and mid‐infrared spectrum (2.5–20 µm), with solar reflectance varying between 87.9% and 19.9%, and mid‐infrared emissivity varying between 90.6% and 10.8%. Consequently, the EC glass can dynamically switch between radiative cooling and solar heating modes. The simulation results show that the architectural application of this EC glass, with climate‐specific operating modes, can achieve a maximum of over 50% annual heating, ventilation, and air conditioning (HVAC) energy savings, contributing to carbon neutrality and sustainable development.